Visualized knowledge mapping on the current research trends and emerging areas of neuroimmune modulation in the past two decades - Han, Xu; Zhou, Yan; Gu, Xiyao (Frontiers in Immunology, 2025)
AimReference data analysis and visualization methods were applied to identify current knowledge mapping methods in the neuroimmune modulation research field.MethodsA comprehensive search of publications within the field of neuroimmune modulation in the Web of Science Core Collection database and PubMed from 2005–2024 was conducted. The reference type was restricted to articles and reviews in the WOSCC database and clinical trials in PubMed. The data were visualized and analyzed via visualization and bibliometric tools, including CiteSpace and VOSviewer.ResultsA total of 5,280 publications were included in the field of neuroimmune modulation. The United States ranked first as the most influential country in terms of both publication number and academic influence. Harvard University had the greatest impact on institutions. The leading scientists in the neuroimmune modulation field have focused on the mechanism at both the peripheral and central levels. Citation analysis and cocitation analysis revealed that acute kidney injury, neuropathic pain, and neuronal regulation are key focal points in neuroimmune research. Furthermore, keyword analysis revealed that “inflammation”, “neuroinflammation”, “microglia”, “cytokines”, “cholinergic anti-inflammatory pathway” and “neuroimmune” had more than 200 co-occurrences and represented research hotspots in this field. A total of 73 clinical trials were identified that targeted neuroimmune modulation to treat diseases. These studies highlighted the central role of the neuroimmune network in diseases, with a particular emphasis on innovative therapies that regulate inflammation through the cholinergic system. Further exploration is needed to develop precise intervention strategies targeting specific cytokines.ConclusionsThis analysis provides comprehensive knowledge mapping in the current research field of neuroimmune modulation. The trends in the field include mechanism studies combined with neuronal regulation. Neuroimmune crosstalk might provide new therapeutic targets for treating nervous system diseases.